Bioaerosol and health assessment in the hospital : a case study of Thammasat Hospital, Thailand - Churairat Puributr; Sajor, Edsel E.; Nowarat Coowanitwong; Perera, L.A.S. Ranjith; Preeda Pakpian; Canada (CIDA); RTG-Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
In last two decades, has witness the adverse health effect of indoor air environment in urban buildings on occupants. Fungal bioaerosol is one of the main indoor air contaminants that can affect health and general well-being. This research is designed to address the understanding about bioaerosol and risk assessment on hospital staff and it recommends ISO 14001 for upgrading the existing environmental protection at the research site in Thammasat hospital, Thailand. The research findings show that the amount of Aspergillus spp. in one of eight studied operation rooms is higher than the standard level. The staff symptoms related to mold exposure at the highest frequency were: runny, blocked or stuffy nose. In this research, the relationship between fungal bioaerosol and respiratory problems were found not to be significant. However, the indoor air in the operation rooms was contaminated with the pathogenic Aspergillus spp. And in the long term, hospital staff are at the potential risk of fungal exposure if this situation is not averted. The research concludes that it is imperative to improve the contaminated indoor air In operation rooms, and to integrate ISO 14001 as a reliable tool of EMS in order to meet micro environmental level standard
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental Management
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Indoor air pollution -- Thailand; Hospitals -- Risk management -- Thailand; Health risk assessment -- Thailand